Prevalence of traumadic dental Injuries among new orthodondic patients seen at the University of Benin Teaching Hospital, Nigeria - I.O. Ajayi; E.O. Uzamere (Nigerian Dental Association, 2015)
Objective: The aim of this study was to determine the prevalence of traumatic dental injuries among new orthodontic patients. Method: The dental records of 150 patients consisting of 57 males (38%) and 93 females (62%) with a mean age of 18.4 ± 7.6 years who presented for orthodontic treatment at the University of Benin Teaching Hospital Dental Centre were assessed for data relating to traumatic Injuries to the permanent anterior teeth. The causes and types of dental trauma, type of tooth involved and number of affected teeth were evaluated with patients' histories, study casts and pretreatment radiographs. Descriptive statistics were performed for the study variables, age and gender differences In the frequency of traumatized teeth were evaluated with the chi-square test. Result: The results revealed dental trauma prevalence of 21.3% among the new patients before the onset of their orthodontic treatment. The prevalence of dental trauma was significantly higher in males (p<0.05) and most frequently observed In patients aged 6 to 10 years. Falls was the commonest cause of dental traumatic Injuries among the patients  (37.5%). The most common type of trauma to the teeth was enamel fracture (46. 9%) followed by avulslon (28.1 %). Most traumatic Injuries affected the right and left maxillary central Incisors. Frequency of trauma to only one tooth was observed in 68.8% of the patients and multiple teeth Involvement seen In 31.2%. Conclusion: This study revealed a high prevalence of traumatic dental injuries among new patients seeking orthodontic treatment at Benin City, Nigeria. An early orthodontic evaluation and interceptive therapy where appropriate is recommended to reduce risk of dental trauma in Nigerian young population.